OPTIMIZATION OF MAINTENANCE PLANS FOR FRAME RELAY EQUIPMENT MAINTENANCE PLANS - Конахович, Г. Ф.; Луцеін, В. І. (Proceedings of National Aviation University, 2021)
The problem of optimization of maintenance plans of network equipment that implements Frame Rich technology, in the form of direct and inverse problem of optimal resource allocation is considered. It is shown that the sequential optimal plan does not have significant advantages over the periodic optimal plan. The use of periodic maintenance plans of data transmission network equipment in operational practice is proposed